The Key Network of mRNAs and miRNAs Regulated by HIF1A in Hypoxic Hepatocellular Carcinoma Cells - Liu, Tong; Tang, Jing; Li, Xiaoyu; Lin, Yuan; Yang, Yuma; Ma, Kai; Hui, Zhaoyuan; Ma, Hong; Qin, Yanyan; Lei, Hetian; Yang, Yanhui (Frontiers in Genetics, 2022)
Purpose: Hypoxia plays an essential role in the progression of hepatocellular carcinoma (HCC), whereas hypoxia inducible factor-1 (HIF-1) is the key transcription factor allowing HCC to survive hypoxia. The aim of this study was to define the essential mRNAs and miRNAs regulated by HIF1A and dissect their functions, interactions, and tumor-infiltrating immune cells in HCC. Methods: A human HCC cell line HepG2 was used as a cell model of HCC. The CRISPR/Cas9 system was used to knock out HIF1A in HepG2 cells, and RNA sequencing was utilized to characterize differentially expressed mRNAs and miRNAs in the HIF1A-knockout HepG2 cells; the identified candidates were then analyzed by GO annotation and KEGG pathway enrichment to study their function and establish a PPI network. Quantitative (q) PCR was used to verify if there were significant differences in the expression of mRNAs, and the association of the selected mRNAs expression with immune cell infiltration levels was further analyzed using The Cancer Genome Atlas (TCGA) pan-cancer data. Results: Using RNA-sequencing, we discovered that there were 1535 mRNAs differentially expressed (adjusted p < 0.05, |fold change|>1.5) in the HIF1A-knockout HepG2 cells, among which there were 644 mRNAs upregulated and 891 mRNAs downregulated. GO annotation and KEGG pathway enrichment showed that these mRNAs were involved in glycolysis/gluconeogenesis, PI3K-Akt signaling pathways, and HIF-1 signaling pathways. In addition, we found that there were 309 miRNAs differentially expressed (adjusted p < 0.05, |fold change|>1.5) in the HIF1A-knockout HepG2 cells, of which there were 213 miRNAs upregulated and 96 miRNAs downregulated. Our further analyses uncovered that these miRNA putative targets were involved in the hippo signaling pathway, axon guidance, and tight junction. Moreover, the construction and analysis of the PPI network showed that OASL, IL6, and TAF1 were recognized as hub genes with the highest connectivity degrees. Importantly, in the HIF1A-knockout HepG2 cells, our qRT-PCR data confirmed the selected mRNA changes revealed by RNA-sequencing, and with TCGA pan-cancer data, we revealed that the expressional levels of these three genes, LUM, SCOC, and CCL2, were associated with immune cell infiltration levels. Conclusion: The identified potential key network of mRNAs and miRNAs regulated by HIF1A in the HCC cells suggests a key role of HIF1A in the tumorigenesis of HCC.